Determinants to the adoption of social media marketing among MSMEs in Tacloban City a case of typhoon resilient MSMEs - Capili, Roselyn A.; Contapay, Damsel M.; Ontuca, Shara C.
The Philippines is a typhoon-prone country due to its geographic location. Hence, business resilience is a critical characteristic that the country's MSMEs must possess in order to continue operating despite the impacts of the disasters. Social media marketing proved to be an essential tool helping in the performance and sustainability of the business, however, MSMEs still lag behind their use of social media marketing. This study aims to examine the determinants of the adoption of social media marketing among typhoon-resilient MSMEs, guided by the TOE framework. This study also investigates the relationship between the adoption of social media marketing and the business resilience of MSMEs in Tacloban City. The data collected from 96 MSMEs were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS-SEM) to determine the relationship among variables and to test the hypotheses of the study. Findings indicate that top management support and environmental uncertainty have a significant influence on social media marketing adoption, while social media marketing adoption also has a strong positive and significant influence on the business resilience of MSMEs. The results call for the adoption of social media marketing on MSMEs in order to improve existing strategies, leverage its usage in the business, and build strong resilience.